Importance of CD44 on umbilical cord mesenchymal stem cells for expansion of hematopoietic cells - Zhang, Y. J; Yang, Y. X; Hu, M. Y; Ni, Q. K; Li, H. G; Miao, Z. C (Cellular and Molecular Biology, 2015)
Human umbilical cord mesenchymal stem cells (hUCMSCs) have important functions on the expansion of hematopoietic stem cells (HSCs) through providing the essential microenvironment for hematopoiesis. In order to test whether CD44 on hUCMSCs could have a key function for the ability of hUCMSCs to expand human HSCs, the soluble anti-CD44 antibody was added to the co-cultures of hUCMSCs and cord blood (CB) CD34+ cells, which blocked the ability of hUCMSCs to expand CB CD34+ cells significantly. Long-term culture initiating cell (LTC-IC) assay revealed that the ability of multipotent differentiation of CB CD34+ cells co-cultured with CD44 knockdown hUCMSCs could only retain lasting at most for 5 weeks in vitro. In vivo assay, based on non-obese diabetic/severe combined immunodeficient disease (NOD/SCID) mice, revealed that the hematopoietic reconstitution potential of CB CD34+ cells co-cultured with CD44 knockdown hUCMSCs is significantly reduced. The hematopoietic supporting ability of hUCMSCs in vivo and in vitro is reduced upon the knockdown of CD44. CD44 has important functions on the ability of hUCMSCs to expand human HSCs in the cell- extrinsic control.